Clarifications of a puzzle: the decline in nutritional status at the onset of modern economic growth in the United States - A'Hearn, B; Komlos, J (Cambridge University Press, 2019)
Bodenhom, Guinnane, and Mroz (2017) are critical of anthropometric research using based on non-random samples. Declining height trends in military and prison data, they argue, are artifacts of negative selection during favorable labor market conditions. We study height trends in the United States in the antebellum decades, which coincided with the onset of modem economic growth. We find that neither the historical evidence nor their own statistical analysis support their views. The decline in physical stature in the decades before the Civil War was real, as Zimran (2019) has also shown.